INTEGRASI LARAVEL DAN METODE SUS DALAM PENGEMBANGAN SISTEM PEMESANAN MAKANAN BERBASIS WEB - Widjanarko, Albertus Raditya Danang (Jurnal Teknik Informasi dan Komputer (Tekinkom), 2025)
The advance of information technology has significantly influenced digital transformation in across numerous industries including the food service sector. This research aims at the designing and evaluating a web-based food ordering information system. The system was developed by using Laravel framework and follows the Model-View-Controler (MVC) architectural pattern, thereby facilitating modularity and efficient data management. The development process had been done through methodical stages: requirements analysis, system design using Unified Modelling Language (UML), implementation of the web-based application, and system testing. Evaluation was undertaken using functional testing (black box) and usability assessment conducted using the System Usability Scale (SUS) methodology. The user feedback was gathered through questionnaires distributed after the system was launched online. The results of the black box testing confirmed that all system functionalities performed in accordance with the stipulated specifications. The usability evaluation produced a SUS score of 71.01, which is classified as acceptable. This indicates that the system meets established usability standards and can be adopted by users with a satisfactory level of confidence and ease. This research aims to contribute to the development of digital service platforms in the food service industry, with an emphasis on enhancing user experience.